(untitled) (Perner’s Contacts, 2009)
This text deals with the level of transport services in chosen Czech regions. For comparing the level of transport services between each region it was necessary to calculate a common coefficient. The calculation modus is explained in the text. The transportation service by bus and train depends basically on the amount of connections and the traveling speed. Finally the result shows a high difference of transport services between chosen regions.